Effectiveness of Intensive Short- Term Dynamic Psychotherapy on Alexithymia in Rheumatoid Arthritis Patients - Kobra Haji alizadeh; Kobra Haji alizadeh; Eghbal Zarei; Fariborz Dortaj (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2021)
Aim and Background: Rheumatoid arthritis is associated with an increased risk of various types of psychological afflictions. Indication of these disorders is added to the erosive factors of chronic disease and has many negative effects on the level of adaptation and mental and social health of these people. This study aimed to evaluate the effectiveness of intensive short-term dynamic psychotherapy (ISTDP) on reducing alexithymia in rheumatoid patients. Methods and Materials: The present research was a quasi-experimental study with pre-test, post-test design as well as control group. In order to select the sample, first of all, based on the criteria of the American Rheumatology Association and the inclusion and exclusion criteria, 40 male and female patients were purposefully selected from specialized rheumatology clinics in Kerman. This selection was made by rheumatologists. The members of the sample group were randomly divided into two 20-memeber groups of experimental and control. For the experimental group, 15 one-and-a-half-hour sessions of intensive short-term dynamic psychotherapy were held. Data were collected through Toronto Alexithymia Scale (TAS). Research data were analyzed using Analysis of covariance. Findings: The findings showed that intensive short-term dynamic psychotherapy is effective in reducing the rate of alexithymia in rheumatoid patients (p <0.05). Conclusions: Patients first performed better in recognizing emotions and then improved their ability to describe emotions and physical symptoms. Intensive short-term dynamic psychotherapy by affecting on anxiety discharge pathway and exact control and moment-by-moment monitoring of anxiety, feelings and defenses helps to reduce clinical symptoms in rheumatoid patients.